Anaerobic codigestion of manipueira with bovine manure for biogas and biofertilizer production - Santos, Elisângela Fernandes dos; Zukowski Junior, Joel Carlos; Serra, Juan Carlos Valdés; Archangelo, Eliane Regina [UNESP]; Sousa, Illys Janes Alves (Elsevier, 2023)
The cassava wastewater called manipueira is the liquid residue obtained from the cassava processing; it is highly polluting and contains toxic elements for both humans and animals. This study aimed at evaluating how different concentrations of bovine manure and manipueira influenced the composition of the biogas and biofertilizer obtained from the anaerobic codigestion process by using batch model digesters. Completely randomized design was used with five treatments and three repetitions. Based on these data, treatment 2 stood out with a higher concentration of methane, being, therefore, the best option for the production of biogas among the studied treatments. Treatment 5 had the highest production of potassium and sodium in the biofertilizer. For the substrate pH, treatments 4 and 5 had values closer to the ideal range for the development of methanogenic bacteria. However, there was no statistically significant difference (P<.05) between treatments for the pH variable of the biofertilizer.
Keywords: alternative energy; anaerobic codigestion; anaerobic digestion; biofertilizer; biogas; Manipueira